The Ikaros transcription factor regulates responsiveness to IL-12 and expression of IL-2 receptor alpha in mature, activated CD8 T cells. - Eric T Clambey; Bernard Collins; Mary H Young; Jens Eberlein; Alexandria David; John W Kappler; Philippa Marrack (PLoS ONE, 2013)
The Ikaros family of transcription factors is critical for normal T cell development while limiting malignant transformation. Mature CD8 T cells express multiple Ikaros family members, yet little is known about their function in this context. To test the functions of this gene family, we used retroviral transduction to express a naturally occurring, dominant negative (DN) isoform of Ikaros in activated CD8 T cells. Notably, expression of DN Ikaros profoundly enhanced the competitive advantage of activated CD8 T cells cultured in IL-12, such that by 6 days of culture, DN Ikaros-transduced cells were 100-fold more abundant than control cells. Expression of a DN isoform of Helios, a related Ikaros-family transcription factor, conferred a similar advantage to transduced cells in IL-12. While DN Ikaros-transduced cells had higher expression of the IL-2 receptor alpha chain, DN Ikaros-transduced cells achieved their competitive advantage through an IL-2 independent mechanism. Finally, the competitive advantage of DN Ikaros-transduced cells was manifested in vivo, following adoptive transfer of transduced cells. These data identify the Ikaros family of transcription factors as regulators of cytokine responsiveness in activated CD8 T cells, and suggest a role for this family in influencing effector and memory CD8 T cell differentiation.